Musik Tradisional Sampek Kalimantan Timur - Sri Ayu Mulyati (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2016)
AbstractThis study aimed to describe organologi and basic techniques of playing traditional musical instruments sampek in East Kalimantan. This study used a qualitative approach to data collection techniques used were observation and interviews. Data analysis was done by the process of categorization, preparation, systematization, and then draw conclusions. Test validation of the data used is source triangulation techniques, techniques da time. Based on this research, it is known that organologi sampek consists of seven parts, the basic techniques of playing sampek have the four stages, and how to play sampek has six stages.Keywords: traditional music, sampek, east kalimantan